2013
DOI: 10.1093/cercor/bhs418
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Attention, Precision, and Bayesian Inference: A Study of Saccadic Response Speed

Abstract: Inferring the environment's statistical structure and adapting behavior accordingly is a fundamental modus operandi of the brain. A simple form of this faculty based on spatial attentional orienting can be studied with Posner's location-cueing paradigm in which a cue indicates the target location with a known probability. The present study focuses on a more complex version of this task, where probabilistic context (percentage of cue validity) changes unpredictably over time, thereby creating a volatile environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 68 publications
10
129
0
1
Order By: Relevance
“…This allowed us to determine the surprise (I S ) associated with each stimulus and the degree of updating (D KL ) on each trial. In addition, we modeled the strength of participants' prior expectations on each trial as the Shannon entropy of the prior distribution (H S ) because behavioral work indicates that saccadic RTs may depend on this factor (21). The H S depended on both the variance of the generative targets' distribution, which was experimentally manipulated, and on learning.…”
Section: Resultsmentioning
confidence: 99%
“…This allowed us to determine the surprise (I S ) associated with each stimulus and the degree of updating (D KL ) on each trial. In addition, we modeled the strength of participants' prior expectations on each trial as the Shannon entropy of the prior distribution (H S ) because behavioral work indicates that saccadic RTs may depend on this factor (21). The H S depended on both the variance of the generative targets' distribution, which was experimentally manipulated, and on learning.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bayesian models with graphical representation have demonstrated great potential in modeling cognitive functions using behavioral data (Mozer et al, 2002; Reynolds and Mozer, 2009a; Shenoy et al, 2010; Shenoy and Yu, 2011; Tenenbaum et al, 2006; Tenenbaum and Xu, 2000; Vossel et al, 2013; Yu et al, 2009) and brain imaging data (Behrens et al, 2007; den Ouden et al, 2010; Ide et al, 2013). In the following, we review recent studies using Bayesian models with graphical representation to model various aspects of cognitive control, including speed-accuracy trade-off (section 2.2), conflict effects in the Eriksen flanker task (section 2.3), and response inhibition (section 2.4).…”
Section: Modeling Cognitive Control Using Bayesian Modelsmentioning
confidence: 99%
“…Given the high flexibility required of cognitive control, it is unclear that those fixed parameters are globally optimal across various experimental configurations. In fact, it has been shown that fixed learning rates are suboptimal in non-stationary environments (Behrens et al, 2007; den Ouden et al, 2010; Vessel et al, 2013). In the next section, we therefore propose a Bayesian model that resolves these two concerns.…”
Section: Modeling Cognitive Control Using Bayesian Modelsmentioning
confidence: 99%
“…Learning the environment’s underlying statistical regularities means that responses to explicitly and predictably cued events are typically faster than to those believed improbable [3134]. This effect is modulated by pharmacological [35,36], surgical [37,38], and neurodegenerative [39] manipulations of ACh.…”
Section: Introductionmentioning
confidence: 99%